Optimizing Public Policy in Developing Digital-Based Pension Funds in Indonesia - Astriawati, Rika (Global Writing Academica Researching and Publishing, 2024)
The increasing elderly population in Indonesia shows the urgent need for effective pension fund development. The gap between pension needs and fund availability adds to the urgency to improve the conventional pension system. The development of digital technology in Indonesia provides an opportunity for transformation in pension fund management, despite challenges in cybersecurity and digital literacy. This study investigates strategies for optimizing public policy in developing digital-based pension funds in Indonesia. The research method used is a qualitative approach, with data obtained from current literature and thematic analysis to understand key issues in policy implementation. The study results found that adaptive policies, government support, and stakeholder collaboration are crucial in accelerating the adoption of digital technology in the pension fund sector. Increasing accessibility and digital literacy are needed to ensure broad inclusion in digital pension services. The use of innovative technologies such as blockchain and big data can improve the efficiency and transparency of the system, while careful monitoring is needed to assess the success of public policies.